SURGICAL MANAGEMENT ON POSTERIOR UVEITIS WITH VITREOUS OPACITY SUSPECTED RETINAL DETACHMENT - Firda Ayu Muthie; Sauli Ari Widjaja; Wimbo Sasono; Muhammad Firmansjah; Ima Yustiarini; Ady Dwi Prakosa; Moestidjab Moestidjab; Gatut Suhendro (Indonesian Vitreoretinal Society, 2020)
Introduction: Posterior uveitis entities are varies between infective or non-infective in aetiology. It can affect the adjacent structures such as retina, vitreous, optic nerve head and retinal blood vessels. Vitreous opacity is the most common features of posterior uveitis and posterior segment evaluation is critical to determine the aetiology and management. Methods: Case report of 32-year-old male with gradual visual loss on right eye since 2 years ago and getting worse 1.5 months before admission. Visual acuity (VA) was hand movement. Posterior segment evaluation revealed vitreous opacity and ultrasound examination showed membrane shaped lesion attached to the optic nerve suggested retinal detachment. Result: Vitrectomy was done for diagnostic and therapeutic purpose. VA was remarkably improved by 6/6 and persist until 6 months post vitrectomy, and progressive improvement on posterior segment. Conclusion: Surgery in the management of posterior uveitis can be divided based on indication, either for therapeutic or diagnostic purposes or to manage its complications. Vitrectomy is one of the modality to manage vitreoretinal complications associated with uveitis